2017
DOI: 10.1093/humupd/dmx039
|View full text |Cite
|
Sign up to set email alerts
|

Combined oral contraceptives and/or antiandrogens versus insulin sensitizers for polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: CRD42016053457.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 128 publications
0
25
0
3
Order By: Relevance
“…According to the quality evaluation of the Cochrane Handbook for Systematic Reviews of Interventions 5.1.0, the following aspects were assessed for all RCTs included in this study: random sequence generation, allocation concealment, blinding of participants and personnel, blinding of outcome assessment, incomplete outcome data, selective reporting, and other bias. The risk of bias was assessed as being high if any of these domains were assessed as being at unclear or high risk of bias.…”
Section: Methodsmentioning
confidence: 99%
“…According to the quality evaluation of the Cochrane Handbook for Systematic Reviews of Interventions 5.1.0, the following aspects were assessed for all RCTs included in this study: random sequence generation, allocation concealment, blinding of participants and personnel, blinding of outcome assessment, incomplete outcome data, selective reporting, and other bias. The risk of bias was assessed as being high if any of these domains were assessed as being at unclear or high risk of bias.…”
Section: Methodsmentioning
confidence: 99%
“…Future high-quality long-term RCTs are needed to confirm these findings. Recent adult systematic review with pairwise meta-analysis showed no statistically important difference between OCP and insulin sensitizers with regard to fasting glucose level only [ 44 ]. The study did not evaluate other glycemic indexes like 2-hour oral glucose tolerance test or hemoglobin A1c.…”
Section: Discussionmentioning
confidence: 99%
“…Treating hirsutism in women is a delicate process and must always be appropriately balanced against the potential adverse effects of the medication used. This being said, many treatment options exist for both young girls, and adult women [29].…”
Section: Discussionmentioning
confidence: 99%